(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
In this article, the thermodynamic and kinetic parameters (Langmuir, Frumkin, and Tyomkin isotherms) of corrosion inhibitor synthesized on the basis of maleic anhydride, monoethanolamine, and phosphoric acid to determine the mechanisms of steel inhibition are studied. According to the results of the research, as the concentration of the inhibitor increases, the level of its coating on the steel surface increases, and its internal energy increases. This shows that the inhibitor protect steel at a high level in various aggressive environments